Psychometric properties of the Greek version of Jacelon Attributed Dignity Scale - Papastavrou, Evridiki; Charitou, Paraskevi; Kouta, Christiana (My University, 2017)
Abstract BACKGROUND: Maintaining dignity is important for successful aging, but there is lack of validated research instruments in the nursing literature to investigate dignity as perceived by the old people. OBJECTIVE: This is a methodological study aiming to investigate the psychometric properties of the Greek version of Jacelon Attributed Dignity Scale as translated in the Greek language. RESEARCH DESIGN: A methodological approach consisting of translation, adaptation, and cross-cultural validation. A sample of 188 Greek-speaking old Cypriot persons drawn from the Hospital outpatient departments was asked to complete the Greek versions of Jacelon Attributed Dignity Scale and the Instrumental Activities of Daily Living. Data analyses included internal consistency reliability (Cronbach's alpha coefficient), item analysis, and exploratory factor analysis using principal component method with orthogonal varimax rotation. ETHICAL CONSIDERATIONS: The study protocol was approved by the National Bioethics committee according to the national legislation. Permission to use the research instrument was granted from the author. Information about the aim and the benefits of the study was included in the information letter. FINDINGS: Cronbach's alpha for Greek version of Jacelon Attributed Dignity Scale was 0.90. Four factors emerged explaining 65.28% of the total variance, and item to total correlation values ranged from 0.25 to 0.74 indicating high internal consistency and homogeneity. Mean item score in Instrumental Activities of Daily Living was 5.6 (standard deviation = 1.7) for men and 6.7 (standard deviation = 1.7) for women, and the correlations between demographics, Instrumental Activities of Daily Living, and the four factors of the Greek version of Jacelon Attributed Dignity Scale were low; also in multiple linear regression, the values of R2 are presented low. DISCUSSION: Demographic characteristics and degree of functionality seem to be associated with some of the dimensions of dignity but with low correlations; therefore, they cannot predict attributed dignity. CONCLUSION: The Greek version of Jacelon Attributed Dignity Scale is a valid and reliable tool to measure attributed dignity in Greek-speaking older adults, but further testing of the psychometric properties and other potential factors that may affect the attributed dignity is needed.
Keywords: Activities of daily living; Dignity; Dignity scale; Older people; Psychometric properties